2020
DOI: 10.1007/s10343-020-00509-3
|View full text |Cite
|
Sign up to set email alerts
|

Residual Efficacy of Pyriproxyfen on Grain Commodities Against Stored Product Insect Pests

Abstract: Studies on residual efficacy of insecticides with reduced risk are necessary for strategies on their use and application frequency. Within these insecticides, insect growth regulators, such as pyriproxyfen, have been successfully used to control stored grain pests. The objective of this study was to evaluate the residual efficacy of pyriproxyfen in larvae of the stored grain pests Oryzaephilus surinamensis, Tribolium castaneum and Trogoderma granarium. Grains of wheat, maize, rice, and oats were exposed to pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Meanwhile, only 0–36% of early-instar and 25–74% of late-instar Asian citrus psyllid, D. citri , survived to adults after exposure to pyriproxyfen [ 53 ]. Adult emergence of stored grain pests, Oryzaephilus surinamensis (L.) , Tribolium castaneum (Herbst), and Trogoderma granarium (Everts), was also reduced when exposed to pyriproxyfen [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, only 0–36% of early-instar and 25–74% of late-instar Asian citrus psyllid, D. citri , survived to adults after exposure to pyriproxyfen [ 53 ]. Adult emergence of stored grain pests, Oryzaephilus surinamensis (L.) , Tribolium castaneum (Herbst), and Trogoderma granarium (Everts), was also reduced when exposed to pyriproxyfen [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, O. surinamensis was found to be more tolerant than T. castaneum when exposed to treatments of surfaces with pyriproxyfen and hydroprene [ 49 ]. In a recent study, Yasir et al [ 25 ] found T. granarium more tolerant compared to O. surinamensis and T. castaneum when larvae of these species were exposed to pyriproxyfen-treated grain commodities.…”
Section: Discussionmentioning
confidence: 99%
“…Arthur and Hartzer [ 14 ] reported that, when the larvae or eggs of T. castaneum or T. variabile were exposed to concrete surfaces on which combined formulations of novaluron and pyriproxyfen had been applied at their labeled rates, no adults emerged in T. castaneum for 16 weeks and emergence did not exceed 25% in T. variabile for 0–8 weeks. Similarly, pyriproxyfen has been found to be effective for 12 weeks when the larvae of T. castaneum , T. granarium and O. surinamensis were exposed to treated grain commodities [ 25 ] and for 8 weeks when larvae of T. castaneum and O. surinamensis were exposed to the treated surfaces [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untreated, clean and infestation free four different grain commodities wheat, maize, rice and oats were obtained from local grain market for use in the treatments. The treatments of grains with concentrations of 0.25, 0.50 and 1.00 mg Kg -1 spinosad diluted in distilled water were performed according to Yasir et al (2020) with few modifications. Briefly, a total of 4.2 Kg grains from each commodity were treated with the each desired spinosad concentrations.…”
Section: Grain Commodity and Treatmentmentioning
confidence: 99%